“My accent is not okay.”: Exploring Thai Students’ Attitudes towards English Accents - Sahrai, Aran; Tantiniranat, Sutraphorn (THAITESOL Journal, 2024)
Native speakers’ accents are generally viewed as models of English accents. However, in real-world communication where English is used as a lingua franca for intercultural communication between people from differing linguistic and cultural backgrounds, English users unavoidably encounter a wide variety of accents. The aim of this research was to investigate the attitudes of Thai students towards native speakers’ accents, Asian accents, and their own accents. A total of 123 Thai students from a public secondary school in Thailand were selected as participants for this study. A verbal-guise test, an online questionnaire, and semi-structured interviews were used to gather data. The study found that American accents were considered the most favorable and the standard for pronunciation. Although Asian English accents were also positively perceived as intelligible and acceptable, some participants expressed negative attitudes toward their own Thai accents, considering them deficient. These results highlight the importance of raising awareness about the diversity of English accents in both English language teaching and policy.